2001
DOI: 10.2514/2.6602
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysics Characterization of Kerosene Combustion

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 10 publications
2
48
0
4
Order By: Relevance
“…In the approximate reaction, the chemical reaction of LOX and RP‐1 can produce the dominant products of carbon dioxide and water vapor (Ebbing & Gammon, ). When it comes to the RP‐1 quasi‐global combustion kinetics mechanism, the listed quasi‐products are CO, H, H 2 , O, OH, and O 2 (Wang, ). Mendillo et al () reported ionospheric TEC depletions due to the launch of NASA's Skylab.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…In the approximate reaction, the chemical reaction of LOX and RP‐1 can produce the dominant products of carbon dioxide and water vapor (Ebbing & Gammon, ). When it comes to the RP‐1 quasi‐global combustion kinetics mechanism, the listed quasi‐products are CO, H, H 2 , O, OH, and O 2 (Wang, ). Mendillo et al () reported ionospheric TEC depletions due to the launch of NASA's Skylab.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…The modeling of JP-8 and other kerosenes is usually achieved using a representative blend of paraffin, naphthene, and aromatic [8,[23][24][25], or by creating a single specie to model the fuel blend [26,27]. For the JP-8 calculations performed using Zhang's model [22], the scheme recommended in the model was used.…”
Section: Modeling Of Pyrolytic Reformingmentioning
confidence: 99%
“…Multiphysics invoked in this effort include turbulence, hydrogen reactions (Wang, 2001) and its associated thermodynamics, convective heat transfer, and surface radiation. The goals of this design are to maintain the 3500 K hot-hydrogen jet as long as possible as it impinges on the sample and to hold the overall chamber wall heat flux below a pre-determined 5 .…”
Section: Design Analysismentioning
confidence: 99%